Аранжировка лексических полей через призму прототипа - Нижегородцева-Кириченко, Лариса; Nizhegorodtseva-Kyrychenko, Larysa (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Статья сфокусирована на теоретическом и практическом аспектах аранжировки вербализованных единиц, которые составляют основной корпус лексико-семантического поля ИНТЕЛЛЕКТУАЛЬНАЯ ДЕЯТЕЛЬНОСТЬ. Также освещаются трактовки прототипических категорий, которые участвуют в моделировании лексических полей. Проанализирована количественная стратификация лексических единиц и лексико-семантических вариантов в пределах схематы лексико-семантического поля ИНТЕЛЛЕКТУАЛЬНАЯ ДЕЯТЕЛЬНОСТЬ. С учетом данных количественного анализа лексико-семантических вариантов, которые именуют парцеллы лексико-семантического поля, представлена модель прототипической категории исследуемого поля. С учетом понятий, эксплицируемых слотами фреймовой модели парцелл, представлена структура прототипической категории ИНТЕЛЛЕКТУАЛЬНАЯ ДЕЯТЕЛЬНОСТЬ. The article is focused on theoretical and practical aspects of arrangement of verbalized units that make the basis of the lexico-semantic field INTELLECTUAL ACTIVITY. Interpretations of prototypical categories that participate in the design of the lexical fields are also highlighted in the article. Quantitative stratification of lexical units and lexico semantic versions is analysed within the limits of schemata of the lexico-semantic field INTELLECTUAL ACTIVITY. Considering the data of quantitative analysis of lexico-semantic variants that name parts of the lexico-semantic field, the model of prototypical category of the investigated field is presented. Taking into account concepts, which are explicated by the slots of frame model, the structure of prototypical category INTELLECTUAL ACTIVITY is proved.
Arrangement of Lexical Fields through the Prism of a Prototype
Keywords: когнитивная лингвистика; фрейм; прототип; лексико-семантические поле; концептуальный анализ; cognitive linguistics; frame; prototype; lexico-semantic field; conceptual analysis